Pelaksanaan Pelayanan Publik Di Kantor Desa Karang Anyar Kecamatan Semendawai Timur - Ibrahim, Ibrahim; Niswah, Choirun; Efendi, Aris (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2024)
Abstract: This research is entitled "Implementation of Public Services at the Karang Anyar Village Office, East Semendawai Subdistrict." The problems that have occurred are that administrative services for population in the village face difficulties in processing the issuance of Family Cards (KK), errors, and a lack of availability of administrative services such as ID cards (KTP), Family Cards (KK), and Birth Certificates. The research method used is qualitative with descriptive characteristics. Data collection techniques include observation, interviews, and documentation. The collected data is then analyzed and presented or data reduction is performed, followed by drawing conclusions. The results of this study show that the implementation of public services has been carried out quite well through several indicators. This includes the reliability of employees who are skilled in using service process aids, reliability seen from their level of education, reliability derived from a wealth of knowledge and experience, and more. Additionally, there is responsiveness in quickly responding to service requests, providing assurance in service delivery, and ensuring timeliness. There is empathy in understanding the needs of the community and attempting to understand their complaints. There are tangible facilities for service at the Karang Anyar Village Office. Furthermore, factors affecting service implementation include the availability of resources, employee awareness, and community support.Keywords: Implementation, Public ServicesAbstrak:Â Penelitian ini berjudul Pelaksanaan Pelayanan Publik di Kantor Desa Karang Anyar Kecamatan Semendawai Timur. Adapun permasalahan yang terjadi, yaitu pelayanan administrasi kependudukan di desa tersebut memiliki kesulitan dalam mengurus pembuatan KK, kesalahan dan kurangnya penyediaan layanan administrasi KTP, KK, Akte Kelahiran. Metode penelitian yang digunakan adalah kualitatif dengan karakteristik deskriptif. Teknik pengumpulan data menggunakan observasi, wawancara dan dokumentasi. Data yang diperoleh kemudian dianalisis dan disajikan kembali atau direduksi data lalu disajikan kemudian ditarik kesimpulan. Hasil penelitian ini menunjukan bahwasanya proses pelaksanaan pelayanan publik sudah dilaksanakan cukup baik melalui beberapa indikator, yaitu dengan melaksanakan kehandalan para pegawai yang handal dalam menggunakan alat bantu proses pelayanan, handal yang dilihat dari jenjang pendidikan, handal yang dimiliki dari banyak wawasan dan pengalaman, dan lainnya. Kemudian ketanggapan dalam merespon cepat pelayanan. Memberikan jaminan dalam pelayanan, jaminan tepat waktu. Empati dengan mengetahui kebutuhan masyarakat, mencoba memahami keluhan masyarakat. Kemudian, berwujud yang berupa fasilitas pelayanan di kantor desa Karang Anyar. Selanjutnya faktor-faktor yang mempengaruhi pelaksanaan pelayanan dengan adanya sarana yang tersedia, faktor kesadaran pegawai, dan juga dukungan dari masyarakat.Kata Kunci:Â Pelaksanaan, Pelayanan Publik